In‐house editorials and journalistic pieces comprise a massive corpus in the scientific literature that can be improved - Ioannidis, John P. A.; Schippers, Michaéla C. (European journal of clinical investigation, 2025)
In‐house editorials and journalistic pieces are massively published in peer‐reviewed scientific journals. This corpus has remained outside the efforts of evidence‐based medicine and research reform, and it can be imbued with unchecked biases. High‐impact journals publish such pieces massively and may generate strong support for specific narratives and perspectives. Pieces with a political slant are also a major issue. Besides high‐impact journals, across the entire scientific corpus, such pieces may be (mis)used to boost impact factors, create implausibly prolific CVs (occasionally even fraudulent) and can be powerful instruments of opinion making favouring some sponsors. Here we propose how this influential literature corpus may be strengthened to maximize its benefits and diminish its potential harms. Helpful measures to consider may include bolstering transparency (on authorship, financial compensation, disclosures of publication‐specific and generic conflicts of interest, handling of political issues, peer‐review, commissioning and timing); self‐regulation with limits per author, improvement of subject matter expertise (with experts, meta‐researchers and methodologists); balance of perspectives (with debates and for choice of topics); and post‐publication review, audit, correction and potential retraction, as needed. A systematic research agenda is needed to study better this phenomenon and also the effectiveness of proposed interventions.